2013
DOI: 10.1002/ase.1417
|View full text |Cite
|
Sign up to set email alerts
|

Can anatomists teach living anatomy using ultrasound as a teaching tool?

Abstract: The utilization of bedside ultrasound by an increasing number of medical specialties has created the need for more ultrasound exposure and teaching in medical school. Although there is a widespread support for more vertical integration of ultrasound teaching throughout the undergraduate curriculum, little is known about whether the quality of ultrasound teaching differs if performed by anatomists or clinicians. The purpose of this study is to compare medical students' evaluation of ultrasound anatomy teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 26 publications
1
77
0
Order By: Relevance
“…Such programs do require a significant initial investment in terms of faculty, equipment and administration; however, if your medical school does not have the resources for this initial investment, the evidence is there to support integrating ultrasound into one topic in the curriculum such as anatomy and building out from this as resources allow. A recurring theme in the papers that employed ultrasound to teach anatomy was the use of ultrasound to teach 'living anatomy' [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such programs do require a significant initial investment in terms of faculty, equipment and administration; however, if your medical school does not have the resources for this initial investment, the evidence is there to support integrating ultrasound into one topic in the curriculum such as anatomy and building out from this as resources allow. A recurring theme in the papers that employed ultrasound to teach anatomy was the use of ultrasound to teach 'living anatomy' [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Gradl-Dietsch et al [98] found no effect of gender on either objective performance during assessment or subjective preference when learning ultrasound. [25][26][27][28][29][30]. US supported teaching addressed cardiac anatomy [33][34][35] most commonly, and several other organ systems [30,32,36].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…The US examination consisted of a systematic longitudinal and transverse multiplanar examination of knee [group 1] and MCP joints [group 2] using a real-time scanner (Logiq E9, GE Medical Systems Ultrasound and Primary Care Diagnostics, Wauwatosa, WI, USA) equipped with a multi-frequency linear matrix array transducer (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Machine settings were optimized before the study and standardized for the whole study.…”
Section: Methodsmentioning
confidence: 99%
“…Employed in many countries, including Spain, the technique is more sensitive and accurate than the physical examination in detecting inflammation in limb joints [4,5]. Furthermore, MSUS has proven to be a useful tool in helping medical undergraduates broaden their understanding of anatomy [6][7][8]. Its use has extended to areas other than rheumatology to enable physicians another perspective on internal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical, or living, anatomy, with the use of living models, has also increased as our understanding of the relationship between the outside and inside of the body has improved, with many schools for instance advocating the use of ultrasound teaching, for instance in anatomy of the neck [24,25] and heart [26].…”
Section: The 19mentioning
confidence: 99%